Quantitative monitoring of aquatic humic substances in Lake Biwa, Japan, using the DAX-8 batch method based on carbon concentrations. (June 2015) - Kida, Morimaru; Maki, Kenzo; Takata, Akihiro; Kato, Taku; Tsuda, Kumiko; Hayakawa, Kazuhide; Sugiyama, Yuko; Fujitake, Nobuhide
Highlights: The average AHS-C ratio increased during the 4 year monitoring period. The water quality may have changed due to the compositional changes of the DOM. AHS also increased the concentration of the DOM in the epilimnion during summer. Both AHS and non-AHS were eluted from the bottom sediment. Abstract: Aquatic humic substances (AHS) have been intensively studied because they have a number of significant biogeochemical functions in water chemistry. In order to evaluate such functions, which are regulated by their quantity and quality, a quantitative understanding of AHS is necessary. This study shows the seasonal and vertical changes in the AHS concentration in Lake Biwa, the largest monomictic lake in Japan, over 4 years. The concentration of dissolved organic matter carbon (DOM-C) and AHS carbon (AHS-C) ranged from 0.85–1.6 mg C/l and 0.32–0.71 mg C/l, respectively. The percentages of AHS-C in the DOM-C ranged from 32% to 65%. At all depths, the DOM-C decreased and the AHS-C slightly increased or remained at nearly the same level, suggesting that the quality of the water may have changed mainly due to changes in the composition of the organic matter. Although the AHS-C to DOM-C ratio fluctuated and had no seasonal tendency, the average AHS-C ratio increased during the 4 year monitoring period. Because AHS can influence the entire food web starting with phytoplankton, unraveling the mechanism by which they accumulate remains an important goal.